Performance-based financing for improving HIV/AIDS service delivery: a systematic review - Suthar, Amitabh B.; Bärnighausen, Till (BMC health services research, 2017)
Although domestic HIV/AIDS financing is increasing, international HIV/AIDS financing has plateaued. Providing incentives for the health system (i.e. performance-based financing [PBF]) may help countries achieve more with available resources. We systematically reviewed effects of PBF on HIV/AIDS service delivery to inform WHO guidelines.
Published: 4 January 2017
Gesehen am 19.06.2018